Single dose oral sulindac for acute postoperative pain in adults. - Moore, R; Derry, S; McQuay, H (2009)
BACKGROUND: Sulindac is a non-steroidal anti-inflammatory drug (NSAID) licensed for use in rheumatic disease and other musculoskeletal disorders in the UK, and widely available in other countries worldwide. This review sought to evaluate the efficacy and safety of oral sulindac in acute postoperative pain, using clinical studies of patients with established pain, and with outcomes measured primarily over 6 hours using standard methods. This type of study has been used for many decades to establish that drugs have analgesic properties. OBJECTIVES: To assess the efficacy of single dose oral sulindac in acute postoperative pain, and any associated adverse events. SEARCH STRATEGY: We searched Cochrane CENTRAL, MEDLINE, EMBASE and the Oxford Pain Relief Database for studies up to June 2009. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled clinical trials of oral sulindac for relief of acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. We planned to use area under the "pain relief versus time" curve to derive the proportion of participants with meloxicam experiencing least 50% pain relief over 4 to 6 hours, using validated equations; to use number needed to treat to benefit (NNT); the proportion of participants using rescue analgesia over a specified time period; time to use of rescue analgesia; information on adverse events and withdrawals. MAIN RESULTS: No studies were identified by the searches that examined oral sulindac in patients with established postoperative pain. AUTHORS' CONCLUSIONS: In the absence of evidence of efficacy, at present, for oral sulindac in acute postoperative pain, its use in this indication is not justified. Because trials clearly demonstrating analgesic efficacy in the most basic of acute pain studies is lacking, use in other indications should be evaluated carefully. Given the large number of available drugs of this and similar classes, there is no urgent research agenda.